Drivers and strategies of international new ventures from a Central European transition economy - Witold Nowiński; Alex Rialp (Journal for East European Management Studies, 2013)
This paper contributes to SME internationalization theory by offering regionspecific propositions on early internationalization of Central and Eastern European (CEE) firms. We suggest that special treatment of international new ventures from CEE transition economies is justified due to constraints faced by their founders, particularly not only limited financial resources but also relatively low human and social capital. We propose that some of the regionspecific drivers which contribute to early internationalization involve domestic market entry barriers and arbitrage opportunities related to the higher purchasing power of consumers from developed economies. Additionally, we find that in order to overcome resource limitations, CEE international new ventures apply effectuation and bricolage to exploit controlled resources and flexibly adapt to the market situation. – – Dieser Artikel trägt zur Theorie der Internationalisierung von KMU mittels regional spezifischer Aussagen über die frühe Internationalisierung mittel- und osteuropäischer Unternehmen bei. Die spezielle Behandlung der 'international new ventures' in diesen Volkswirtschaften erscheint aufgrund von spezifischen Einschränkungen für ihre Gründer, vor allem aber aufgrund von begrenzten finanziellen Mitteln und geringem Human- und Sozialkapital gerechtfertigt. Die regional spezifischen Treiber, die zur frühen Internationalisierung beitragen, schließen inländische Markteintrittsbarrieren und Arbitrage-Möglichkeiten in Bezug auf die höhere Kaufkraft der Verbraucher aus den entwickelten Volkswirtschaften mit ein. Darüber hinaus nutzen die 'international new ventures' der Region Effektuierung und Bricolage, um Einschränkungen im Bereich der Ressourcen zu überwinden, die kontrollierten Ressourcen zu nutzen und sich flexibel an die Marktsituation anzupassen.
Keywords: 650; internationalization; international new ventures; SMEs; transition economies; effectuation; bricolage; KMU; Globalisierung; Unternehmensgründung; Systemtransformation; Osteuropa